Modern Conflict, Transnational Migration and the Experiences of a Sudanese Youth (Groundings Undergraduate, 2024)
This paper explores the experiences of a Sudanese youth through interviews and analysis, tracing their journey from conflict in their home country to transnational immigration. The objective is to humanise the collective immigrant experience, particularly in the context of modern conflict and migration. Originating as an assignment on oral history, the research employs an interdisciplinary oral historical methodology for data analysis. Integration of linguistics and psychology with oral history methods is emphasised, facilitating a nuanced understanding of the interview transcripts and the socio-political implications of the discussed topics. Additionally, the paper contextualises the interview findings within relevant secondary literature to deepen comprehension. Lastly, it examines the socio-political climate of 21st-century Europe concerning immigration influx, challenging stereotypes and highlighting the complexity of collective experiences. From facing terrorisation from a tyrannical regime and its secret police to being stranded on the Mediterranean and travelling Europe, this paper examines the story of a young Sudanese man.
Keywords: Thematic Analysis; Subject Interview; Independent Research; Human Security; UK Politics; Migration